2022
DOI: 10.3390/ijms231911778
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Potential of Naturally Occurring Peptides in Counteracting SH-SY5Y Cells Injury

Abstract: Peptides have revealed a large range of biological activities with high selectivity and efficiency for the development of new drugs, including neuroprotective agents. Therefore, this work investigates the neuroprotective properties of naturally occurring peptides, endomorphin-1 (EM-1), endomorphin-2 (EM-2), rubiscolin-5 (R-5), and rubiscolin-6 (R-6). We aimed at answering the question of whether well-known opioid peptides can counteract cell injury in a common in vitro model of Parkinson’s disease (PD). Antiox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…However, when SH-SY5Y cells were treated with 6-OHDA in the presence of peptides (0.1 − 10 µM), R-6 and its four analogs ( 1 , 3 , 5 and 7 ) exhibited the capacity to recover the cell death induced by neurotoxin treatment. Parent peptide increased the cell viability at 20% (at the lowest dose) [ 17 ], while analog 1 at 30% (at the dose of 10 µM), 3 at 15% (at the dose of 1 and 10 µM, respectively), 5 in 14 − 27%, 7 in 22 and 27% (at the dose of 1 and 10 µM, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when SH-SY5Y cells were treated with 6-OHDA in the presence of peptides (0.1 − 10 µM), R-6 and its four analogs ( 1 , 3 , 5 and 7 ) exhibited the capacity to recover the cell death induced by neurotoxin treatment. Parent peptide increased the cell viability at 20% (at the lowest dose) [ 17 ], while analog 1 at 30% (at the dose of 10 µM), 3 at 15% (at the dose of 1 and 10 µM, respectively), 5 in 14 − 27%, 7 in 22 and 27% (at the dose of 1 and 10 µM, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, our previously published neuroprotective study showed that R-6 possesses neuroprotective potential in the neuroblastoma cells (SH-SY5Y) damage model caused by 6-hydroxydopamine (6-OHDA) treatment [ 17 ]. When SH-SY5Y cells were treated with 6-OHDA (100 µM) in the presence of R-6 (0.1–10 µM) for 24 h, we observed a significant capacity to recover the neurotoxicity induced by neurotoxin treatment.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of resistance, traditional antibiotics are becoming increasingly ineffective, necessitating the development of better antimicrobial alternatives. In addition to existing treatment strategies, such as using conventional antibiotics used to target protein synthesis [ 4 ], antimicrobial peptides (AMPs) are thought to be a feasible alternative for eliminating multidrug-resistant bacteria because their mode of action differs from that of currently available antibiotics; they disturb cell membrane integrity [ 5 , 6 ], impede protein [ 7 , 8 , 9 , 10 , 11 ] and cell wall formation [ 12 , 13 , 14 , 15 ], and alter enzyme function [ 10 , 16 , 17 ]. AMPs can be used for simultaneous or subsequent treatments in many bacterial illnesses as they have independent therapeutic efficacies and fewer adverse effects than conventional antibiotics [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bioactive peptides (BPs) are short chains of 2 to 50 amino acids with a molecular weight of less than 10 kDa exerting biological effects on unicellular and multicellular organisms [1,2]. Their biological properties make them useful as potential candidates for the treatment of pathologies where conventional medication is ineffective or not advised [3,4]. BPs can have several beneficial functions such as anti-inflammatory, antihypertensive and antidiabetic [1].…”
Section: Introductionmentioning
confidence: 99%